The 'third class' of medications: Sales and purchasing behavior are associated with Pharmacist only and Pharmacy Medicine classifications in Australia - Emmerton, Lynne (2009)
Objective: Nonprescription (over-the-counter) medications in Australia are classified as Pharmacist Only Medicines, Pharmacy Medicines, or unscheduled medications. This report characterizes these medication classifications using key sales and purchasing behavior variables. Design: Descriptive, nonexperimental, cross-sectional study. Setting: 15 pharmacies in southeast Queensland, Australia, with data recorded over 36 hours per pharmacy in mid-August, 2006. Participants: Eligible purchasers (n = 3,470 medication purchases) of all non-prescription medications (including nutritional supplements). Intervention: Researchers documented details of all observed nonprescription medication sales and interviewed all available patients following the transaction. Main outcome measures: Incidence of product-related consultation, products purchased (brand, dosage form, classification), and purchasing behavior data (including previous purchase, intended use, intended user, and intention to purchase a particular brand). Results: More restrictive classification of the purchased medication was significantly (P < 0.01) associated with younger purchasers, purchase of a single nonprescription medication, intent to self-use the medication, intent to purchase a particular brand, repeat purchase, brand-switching interventions by pharmacy staff, pharmacy staff influence on first-time purchases, and observed consultation by pharmacists. Legislative compliance issues were identified: Pharmacists consulted in only 54.7% of Pharmacist Only Medicine sales and 13 cases (1.7% of observed sales) occurred in which Pharmacist Only and Pharmacy Medicines had been sourced from publicly accessible areas of the store. Conclusion: Pharmacist Only Medicines received greater levels of professional involvement during their sale than Pharmacy Medicines and unscheduled medications, despite higher levels of product familiarity among patients. To optimize the benefits of this classification system, emphasis on professional guidelines is recommended.